2008
DOI: 10.1364/oe.16.006417
|View full text |Cite
|
Sign up to set email alerts
|

Analytical vectorial structure of hollow Gaussian beams in the far field

Abstract: The analytical vectorial structure of HGB is investigated in the far field based on the vector plane wave spectrum and the method of stationary phase. The energy flux distributions of HGB in the far-field, which is composed of TE term and TM term, are demonstrated. The physics pictures of HGB is illustrated from the vectorial structure, which is important to understand the theoretical aspects of both scalar and vector HGB propagation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
32
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(32 citation statements)
references
References 0 publications
0
32
0
Order By: Relevance
“…Up to now, much work has been done on HGBs because it is a convenient and powerful tool to describe and treat dark hollow beams with circular symmetry. The propagation properties of HGBs have been studied in detail [14][15][16][17][18]. However, all previous theoretical models of HGBs are related to the fully coherent case.…”
Section: Introductionmentioning
confidence: 99%
“…Up to now, much work has been done on HGBs because it is a convenient and powerful tool to describe and treat dark hollow beams with circular symmetry. The propagation properties of HGBs have been studied in detail [14][15][16][17][18]. However, all previous theoretical models of HGBs are related to the fully coherent case.…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that radial polarization to be the preferred approach for pupil masks for super resolution and apodization at high NA [7]. Recently, hollow Gaussian beam (HGB) has attracted much attention due to its properties and applications [8][9][10][11][12][13][14][15][16][17][18][19]. It was found that the area of the dark region across the HGBs can be easily controlled by proper choice of the beam parameters [11].…”
Section: Introductionmentioning
confidence: 99%
“…The propagation, farfield intensity distribution, and M2 factor of HGB through paraxial systems have been investigated in detailed [12][13][14][15]. In addition, the nonparaxial propagation of vectorial HGBs in free space is also studied based on the vectorial Raleigh-Summerfield diffraction integral [16], and the analytical vectorial structure of HGB is investigated in the far field based on the vector plane wave spectrum and the method of stationary phase [17]. On the other hand, singular optics studying optical vortices, or phase singularities, has grown rapidly recently because optical vortices have some interesting properties [18][19][20] and promising applications [21][22][23][24], for instance, optical vortices can be used to construct highly versatile optical tweezers.…”
Section: Introductionmentioning
confidence: 99%
“…Followed by the advent of HGB, a rich amount of investigations about HGB have been increasingly presented. For example, the propagation properties of HGB through apertured paraxial optical systems [10] and a turbulent atmosphere [11] have been studied, radiation forces produced by highly focused HGB have also been discussed, and the analytical vectorial structure of HGB in the far field has been studied by Wu et al [12] more recently.…”
Section: Introductionmentioning
confidence: 99%